Enhanced High‐Temperature Strength of a Low‐Density Dispersion‐Strengthened Fe–Mn–Al–C Steel. Issue 5 (4th December 2021) - Wu, Zhiqiang; Hasan, Md Nzmul; Zhou, Honggang; Hu, Jun; Liu, Longfei; Lu, Liwei; An, Xianghai
Abstract : A novel low‐density dispersion‐strengthened Fe–18%Mn–8%Al–0.8%C (wt%) steel exhibiting superior high‐temperature strength at 700–900 °C, is developed. The finely dispersed ferritic grains that form near the grain boundaries of the austenite phase provide significant strengthening by pinning the dislocations and enable high microstructural stability by restricting the dynamic recovery/recrystallization. The high Mn content provides remarkable solid solution strengthening to this steel, while the high aluminum content prominently lowers the density to enhance the specific strength. This newly developed steel with low alloying and manufacturing costs has great potentials for structural applications at elevated temperatures. Abstract : A novel low‐density dispersion‐strengthened Fe–18%Mn–8%Al–0.8%C (wt.%) steel, exhibiting superior high‐temperature strength at 700–900 °C, is developed. The finely‐dispersed ferrites that form near the grain boundaries of the austenite phase provide significant strengthening by pinning the dislocations and enable high microstructural stability by restricting the dynamic recovery/recrystallization. This cost‐effective steel has great potentials for high‐temperature structural applications.